Strategic Succession Plan to Expand the Sustainability of Saluyu Berkah Store: Linking and Integrating Education - Komalasari, Fira; Nurbayanti, Resti; Rifandi, Rifan Ahmad; Julajizah , Nita; Fauziyah, Azizah (Journal Corner of Education, Linguistics, and Literature, 2024)
The ability to endure and thrive is contingent upon the previous generation's preparedness in formulating a comprehensive strategy for the succession process. This study aims to identify the factors that influence business sustainability and to pinpoint effective strategies that successors can employ to enhance performance and competitive strength. The research utilizes a qualitative methodology, focusing on "Toko Berkah Saluyu," located in Kuningan Regency, West Java, with participation from the owner's child. Data was gathered through in-depth interviews with the potential successor. The analysis employed an interactive model approach. The findings indicate that the candidate successor is prepared to carry on the family business, which is characterized as a family-owned and managed enterprise designed to operate and expand across generations. However, it is uncommon for family businesses to have successors who are adequately prepared, possessing both a solid educational background and a strong motivation to continue the family legacy. Furthermore, the research suggests that "Toko Berkah Saluyu" should enhance its succession planning by recognizing the significance of motivation in the succession process, thereby allowing the next generation to cultivate innovative ideas.